COUTINHO, Eduardo. Literatura Comparada na América Latina: ensaios. - Machado, Ronaldo (Organon, 2004)
COUTINHO, Eduardo. Literatura Comparada na América Latina: ensaios. Rio de Janeiro:EDUERJ, 2003, 130p.Resenhado por: Ronaldo Machado